IDENTITAS GAY KULIT HITAM DI AMERIKA SERIKAT DALAM FILM MOONLIGHT - Fatmawati Fatmawati (Haluan Sastra Budaya, 2019)
This article aims to examine the identity of a gay African American in the United States portrayed in the Moonlight movie. It uses representation about identity theory which reading Judith Butler's queer approach. The results show the transformation of main character's identity reflected througout his life and his reflectivity to face and overcome any circumtances. He slowly fights back again discrimination and becomes a strong man as well as free from discrimination.